Communication systems and techniques - Schwartz, Mischa (IEEE Press, 1996)
An introductory, graduate-level look at modern communications in general and radio communications in particular. This seminal presentation of the applications of communication theory to signal and receiver design brings you valuable insights into the fundamental concepts underlying today's communications systems, especially wireless communications. Coverage includes AM, FM Phase Modulation, PCM, fading, and diversity receivers.